(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This research paper aims to know modern technology and digital transformation and use it to attract and attract new skills and competencies to banks and train workers in the banking sector to use technology in order to facilitate services for customers and provide technological services that lead to attracting new customers. Therefore, it was necessary to know what artificial intelligence is. And machine learning and modern technologies and how to train workers in the banking sectors and develop their competence and skills, as well as the opportunities and challenges presented by this technology in order to develop a proposed business model that helps overcome the obstacles and difficulty of attracting talent in the workplace at the present time, as well as relying appropriately on What is called competency planning and developing plans to train employees on this technology to raise the level of competencies in banks and thus provide better services to customers. A set of questions were prepared and directed in the form of a personal interview to the selected study sample of 50 employees from different banks in Baghdad Governorate. The data was analyzed, and it indicated The results of the study indicate that the percentage of males in the study sample compared to males is a large percentage of 70%. We see that females have more interest in development and use of modern technology, training and career development, and that training and learning increases loyalty and belonging to the banking institution.